STUDENT-CENTERED APPROACHES TO TEACHING SPEAKING IN THE ENGLISH CLASSROOM (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines how student-centered approaches in English classrooms foster speaking proficiency. It explores the role of peer interaction, collaborative tasks, and learner autonomy in developing oral skills. The paper contrasts traditional teacher-fronted methods with student-centered instruction and demonstrates the latter's greater effectiveness in boosting learner engagement and confidence. The findings indicate that student-centered activities increase students' willingness to speak, improve fluency, and promote communicative independence.